Explorations in historiographies of geographical knowledges - Gerike, Matthew J. (Kansas State University, 2012)
Geographers, as part of their work as scholars and academics, continually “do” geography. Geography is practiced as research when tools, perspectives, and techniques are applied to problems or areas of study, exploring, understanding, and building geographical information. Geography is practiced as a social discipline when geographers interact with those around them, sharing geographical knowledge through writing, publishing, presenting, teaching, and discussion so others can read, listen, and engage. In doing geography – continuously practicing research and engaging in the documentation and communication of geographical knowledge – geographers also actively continuously construct the history of geography. These incidences, slides, and pages of knowledges are the foundation and structure of geography as a practiced discipline. Research explored the historiographies of geographical knowledges in presidential addresses of the Association of American Geographers, thematic conceptualizations of the subfield of cultural geography, and representation of women across editions of introductory human geography textbooks through content analysis and spatial. Conclusions strongly support the contention that geographic knowledges and the nature of geographic thought actively evolve as contemporary scholars practice their profession. By paying attention to these constructive processes and understanding their interactive role in it, geographers are better informed of the history of their specialty and their direct and vested role in the enterprise.
Keywords: Geography; History of geography; Cultural geography; Human geography; Textbooks; Geographical knowledges; Geography (0366)